2009
DOI: 10.1038/ejhg.2009.7
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of tightly linked SNPs in screening step of genome-wide association studies leads to increased power

Abstract: Recent developments in genome-wide association studies (GWAS) have lead to the localization of disease genes for many complex diseases. The scrutiny of the respective publications reveals, first, that statistical analysis is restricted typically to single-marker analysis in the first step, and that, second, the presence of multiple, independently associated SNPs within the same linkage disequilibrium (LD) region is a common phenomenon. Motivated by this observation, we show through a power simulation study tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 79 publications
3
16
0
Order By: Relevance
“…Haplotype-based algorithms were developed to cope with multiple comparison problems in GWAS at multiple SNP loci in LD. 29 Permutation testing is another approach to confront the problem of multiple comparisons, 30 because this method accounts for the exact correlation between tests and does not overcorrect by assuming that all tests are independent; hence, it is more powerful than family-wise type I error and FDR methods of correction. Recent reports suggest that the application of both haplotypebased and individual-SNP testing to GWAS should be adopted as a routine procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Haplotype-based algorithms were developed to cope with multiple comparison problems in GWAS at multiple SNP loci in LD. 29 Permutation testing is another approach to confront the problem of multiple comparisons, 30 because this method accounts for the exact correlation between tests and does not overcorrect by assuming that all tests are independent; hence, it is more powerful than family-wise type I error and FDR methods of correction. Recent reports suggest that the application of both haplotypebased and individual-SNP testing to GWAS should be adopted as a routine procedure.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reviewed that the presence of multiple independently associated SNPs within one gene is a common phenomenon [30] . None of the methods described above makes proper use of independent signals that remain after adjustment for LD.…”
Section: Gene and Pathway Scoresmentioning
confidence: 99%
“…One would then expect a haplotypic test to have higher power than a single-marker test for detecting an ungenotyped low frequency causal variant. Indeed, a previous simulation study suggests that multimarker tests can have higher power than single-marker tests, 5 and a previous genome-wide haplotypic study found a gene cluster associated with coronary artery disease that was not found with genome-wide SNP testing. 6 One haplotype association test with appealing properties is the Beagle haplotype cluster test.…”
Section: Introductionmentioning
confidence: 99%